Elazığ ili çimento fabrikasının çevresinde yetişen prunus armeniaca l. (kayısı) bitkisi polenlerinin in vitro çimlenme ve tüp büyümesinin araştırılması - Gür, Nazmi; Topdemir, Aykut; Topdemir, Gülşah (My University, 2012)
In this research which has been done in order to examine the polen growth and tube elongation of apricot (Prunus armeniaca L.) plants located in downtown area of the southern province of Elazig Cement Plant in other distances up to 2500 meters of 500 meter intervals. Brawbaker Kwack medium used in the experiments were used to germinate the pollens. By the 2500 meters to 500 meters of pollen germination percentage was 13.64, falling 70.26%. The length of the tube in a similar way to 2500 m in 359.6 ?m, while 500 meter 23 ?m, it went down to the tube length of approximately 93.6% percent had a reduction.
Bildiri - Yayımlanmış
Keywords: Cement plant; apricot (Prunus armeniaca L.); polen germination; polen tube growth